(untitled) (Journal of Governance and Development (JGD), 2024)
Agrarian conflict is inevitable, considering that Indonesia is known as an agricultural country. One of the agrarian conflicts that takes place continuously is the conflict that occurred in Banyuwangi, namely between PT. Bumi Sari with the Farmers Pillar of Pakel Village. This conflict involves the Company and civil society. The purpose of this study is to analyze the authority of the Banyuwangi local government in realizing the Protection of Agricultural Land and Food (PLP2B) in reducing agrarian conflicts as an effort to create Sustainable Development Goals (SDGs) in Banyuwangi, Indonesia. This study actualizes the juridical normative model with the types of statute approach and conceptual approach. The study consisted of primary data and secondary data. Primary data comprises PLP2B, SPPN, PPA, and Regional Government Law, while secondary data contains various journls and books. Data analysis includes data collection, data reduction, and conclusions drawn. The data analysis of this study uses the theory of autonomy. Concluding uses an inductive pattern (generalization). The study results stated that after enacting the Job Creation Law, which imposed PSN (National Strategic Program), it could precede PLP2B in running a program. The Banyuwangi local government has the authority to ratify the PLP2B Law through the function of regional autonomy as an implication of the concept of decentralization in Indonesia’s government system. The Banyuwangi Regency government should optimize this function to create regulations or programs that have a relationship or correlation with the resolution of agrarian conflicts.